Association of Variants in PLD1, 3p24.1, and 10q11.21 Regions With Hirschsprung’s Disease in Han Chinese Population - Niu, Wei-Bo; Bai, Mei-Rong; Song, Huan-Lei; Lu, Yan-Jiao; Wu, Wen-Jie; Gong, Yi-Ming; Yu, Xian-Xian; Wei, Zhi-Liang; Yu, Wen-Wen; Gu, Bei-Lin; Cai, Wei; Chu, Xun (Frontiers in Genetics, 2020)
Background and Aims: Hirschsprung’s disease (HSCR) is a rare genetically heterogeneous congenital disorder. A recent study based on whole genome sequencing demonstrated that common variants at four novel loci were associated with HSCR susceptibility, which contained two intronic variants on CASQ2 and PLD1, and intergenic variants located between SLC4A7 and EOMES at 3p24.1, and between LINC01518 and LOC283028 at 10q11.21. To validate these associations with HSCR susceptibility, we performed a case-control study in a Han Chinese sample set. Methods: We selected four previously identified SNPs for replication, along with tag SNPs to cover the four associated regions. In total, 61 SNPs were genotyped in 420 HSCR patients and 1,665 healthy controls of Han Chinese population. Results: None of the 14 tag SNPs in CASQ2 gene region, including the previously associated rs9428225, showed association with HSCR. Among the 24 tag SNPs from SLC4A7-EOMES region at 3p24.1, rs2642925 (odds ratio (OR) = 1.41, 95% confidence interval (95% CI) = 1.10-1.79; P Additive = 0.007) and the previously associated SNP rs9851320 showed suggestive association (OR = 1.22, 95% CI = 1.01-1.47; P Additive = 0.042). A non-synonymous SNP rs2287579 in PLD1 showed suggestive association with HSCR susceptibility (OR = 1.71, 95% CI = 1.18-2.46; P Additive = 0.004). Additionally, the previously associated PLD1 SNP rs12632766 showed a suggestive significance (OR = 1.20, 95% CI = 1.01-1.42, P Additive = 0.038). In the LINC01518-LOC283028 region at 10q11.21, three SNPs meet the study-wide significance threshold. Rs17153309 was the most associated SNP (OR = 1.60, 95% CI = 1.34-1.90; P Additive = 1.13×10-7). The previously associated SNP rs1414027 also showed significant association (OR = 1.43, 95% CI = 1.20-1.70, P Additive = 3.92×10-5). Two associated SNPs at 10q11.21 (rs1414027 and rs624804) were expression quantitative trait loci (eQTLs) in digestive tract tissues from GTEx databases. Conclusions: Our results confirmed that variants of LINC01518-LOC283028 region were associated with HSCR in Han Chinese population. Additionally, the susceptibility SNPs in LINC01518-LOC283028 region were associated with the expression levels of nearby genes. These results provide new insight into the pathogenesis of HSCR.